Pengaruh Belanja Barang dan Jasa, Belanja Modal, Belanja Pegawai dan Investasi Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Selatan - Pangestu, Eka Cindy (PPJP ULM, 2018)
This research is done for to find out whether goods and services expenditures,capital expenditures, employee expenditures, and investments have an effect on EconomicGrowth in South Kalimantan Province with the dependent variable of Economic Growthand the independent variable is Expenditure of Goods and Services, Capital Expenditure,Employee Expenditure, and Investment. The data used is time-series data, which is the period 2006 until 2011. Theanalysis used is the multiple linear regression method. The results of this study indicate that the variables of Capital Expenditures andEmployee Expenditures Significant Influence on Economic Growth in South KalimantanProvince, the government's suggestion to overcome the economic slowdown of SouthKalimantan is the Expenditure of Goods and Services accompanied by efforts to improvethe quality of policy support programs such as increasing the quantity and quality offacilities and infrastructure to increase investor interest to invest so that good impact oneconomic growth, while the value of determination coefficient of 0.776 this means thattogether independent variables affect the dependent variable.